2003
DOI: 10.2486/indhealth.41.181
|View full text |Cite
|
Sign up to set email alerts
|

Health Survey on Workers and Residents Near the Municipal Waste and Industrial Waste Incinerators in Korea.

Abstract: Hazardous substances, such as polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) also have been detected in Municipal Solid Waste (MSW)and industrial waste incinerators in Korea. In this study, we estimated the exposure status of these hazardous substances and their heath effects in workers and residents near the MSW incinerators and residents near the industrial waste incinerators. We interviewed 13 workers and 16 residents from the area around the two MSW incinerators, and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…In the current study, the mean PCDD/F concentration for all workers was 2.5 ng I-TEQ/kg lipid, while that corresponding to plant workers was 2.1 ng I-TEQ/kg lipid, which is remarkably lower than that found by Kim et al (2005b) 70.1 ng I-TEQ/kg lipid. The current mean PCDD/F concentration is also lower than those found in most of the above studies concerning blood of workers in MSW/infection incinerators (Hu et al 2004;Kumagai and Koda 2005;Kim et al 2005b;Chen et al 2005), while are similar to those reported by Leem et al (2003). Recently, Ichiba et al (2007) reported the concentrations of urinary 1-HP in 100 workers of three MSWIs and one HWI, before and after their work shifts.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the current study, the mean PCDD/F concentration for all workers was 2.5 ng I-TEQ/kg lipid, while that corresponding to plant workers was 2.1 ng I-TEQ/kg lipid, which is remarkably lower than that found by Kim et al (2005b) 70.1 ng I-TEQ/kg lipid. The current mean PCDD/F concentration is also lower than those found in most of the above studies concerning blood of workers in MSW/infection incinerators (Hu et al 2004;Kumagai and Koda 2005;Kim et al 2005b;Chen et al 2005), while are similar to those reported by Leem et al (2003). Recently, Ichiba et al (2007) reported the concentrations of urinary 1-HP in 100 workers of three MSWIs and one HWI, before and after their work shifts.…”
Section: Discussionsupporting
confidence: 74%
“…However, studies concerning internal exposure of workers employed in these facilities are rather scarce. In addition, most of these studies have been carried out in workers at municipal waste incinerators (Hours et al 2003;Leem et al 2003;Kumagai et al 2004;Hu et al 2004;Charbotel et al 2005;Kim et al 2005a;Shih et al 2006b;Yoshida et al 2006), and excepting a survey performed in Germany, in which the levels of a number of metals and organic substances (PCBs, HCB, CLPs, 1-HP, BTEX) were biologically monitored (Angerer et al 1992), the remaining studies were mainly focused on determining PCDD/F concentrations in blood (Kumagai and Koda 2005;Moon et al 2005;Shih et al 2006a, b). Studies concerning the internal exposure of workers at industrial or hazardous waste incinerators are particularly scarce.…”
Section: Discussionmentioning
confidence: 98%
“…Null hypothesis is rejected. This result is supported by the findings of Lee et al [7] that workers safety practices within an industry has a direct effect on their health and safety. A worker may be instructed to wear personal protective equipments which he or she may not comply with when there are no strict instructions.…”
Section: Hypothesissupporting
confidence: 81%
“…Null hypothesis is rejected. This result is supported by the findings of Lee et al [7] who estimated the exposure status of hazardous substances and their health effects in workers and residents near a municipal solid waste (MSW) incinerators and residents near the industrial waste incinerators in Korea. They found that workers around industrial waste incinerator are exposed to hazardous substance such as Polychlorinated dibenzo-p-dioxins (PCDD) which causes respiratory infections and diarrhoea diseases.…”
Section: Research Instrumentsupporting
confidence: 81%
“…ROS are induced by endogenous oxygen metabolism in cells and by various environmental pollutants, which damage cellular macromolecules such as DNA, RNA and protein 2) . Hazardous substances such as polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), mercury vapors and other silicates have been demonstrated to involve the production of plasma malondialdehyde (MDA) 3,4) , which is one of the products of lipid peroxidation 5) . Therefore, exposure to those hazardous substances may elicit ROS.…”
mentioning
confidence: 99%